Oralidade e letramento no ensino de Língua Portuguesa : uma proposta de trabalho com o gênero relato pessoal - Dantas, Sônia Alves (2015)
This study began from the verification that oral and written teaching, in most of the Brazilian schools, is still happening in an unsatisfying way, either for the artificiality in education proposals on genres of discourse which not always concern real situations of the language uses or for the small space reserved to the education for oral genres at the school. Thus, the main objective of this research was to analyze the possible contributions of a didactic sequence of the genre of discourse known as personal tale to the extension of communicative skills from 6th grade students of elementary school. Moreover, it was specifically aimed: to promote a discussion regarding the relevance of studying oral genres; to promote a brief reflection about the relevance of the work with genres as a teaching tool, emphasizing the importance of booking larger space also to work with oral genres; to foster a brief reflection about the contributions of Educational Sociolinguistics to teach Portuguese and, specifically, about the importance of an oriented work toward the notion of linguistic adequacy, as a way to fight against the error doctrine and, consequently, against linguistic prejudice; to present a proposal of didactic intervention made with 6th grade students from an elementary public school from Uberlândia/MG and analyze the results of its application; to contribute with teacher formation, by editing didactic material for Portuguese lessons and also regarding reflection about the proposal application and its outcomes. For this purpose, a qualitative research was developed, which can also be defined as an action research, considering its interventionist and interpretative character. Therefore, this research involved the participation of fifteen students from the 6th grade from an elementary public school from Uberlândia/MG, in addition to the researcher teacher. For two months, there were developed teaching activities about orality and writing provided in the didactic sequence proposed. After this, the analysis of the data that formed the corpus of the research has been performed: oral and written text productions of students and field notes from the researcher teacher on the development of the proposed activities. Data analysis was carried out highlighting theoretical authors, such as Bakhtin (1997), Cyranka (2014), Dolz, Noverraz and Schneuwly (2004), Faraco (2008), Fávero, Andrade & Aquino (2012), Geraldi (2004), Marcuschi (1997; 2001; 2010), among others. The outcomes pointed out that the didactic sequence of work with the genre of discourse Personal Tale is an important teaching tool, since it improved the works with the modalities speaking and writing in a real situations of language use and, thus, contributed to greater engagement of the students in activities performed and the consequent improvement of oral and written text productions of the students.